PENERAPAN PEDEKATAN SAINTIFIK DENGAN TUTOR SEBAYA UNTUK MENINGKATKAN PEMAHAMAN MATEMATIKA SISWA KELAS VIIA MTs AL-MUNAWAROH MERAUKE - Ruslau, Maria Fransina Veronica; Suryani, Dessy Rizky; Mutmainnah, Linda Za’farani (Universitas Papua, 2018)
This research aimed to improve student’s mathematical understanding through the scientific approach and peer tutor model. This research was classroom action research that was done in 2 cycles. Every cycle divided into 4 parts that were planning, action and observation, and reflection. The subject of this research was students’ grade VIIA MTs Al-Munawwaroh Merauke that consists of 25 students. The technique of data collection was used test observation and questionnaire of students learning motivation. The research result showed that the average of the students increased in every cycle and classical completeness of the cycle I was 64% and cycle II 88% from that result showed that an increase classical of cycle I and cycle II. Students activity increase on cycle I 60% with active category and cycle II obtained 84% with active category and extremely active. Then can be said that the scientific approach and peer teaching model can improve students’ understanding of mathematics class VIIA MTs Al-Munawaroh Merauke. DOI: https://doi.org/10.30862/jhm.v1i2.1044